THE APPLICATION OF MURABAHAH CONTRACTS IN THE INSTALMENT SERVICES OF DHUAFA PARTNER COOPERATIVES IN INDONESIA - Ali, Saifullah; Amalia, Zalva; Yusuf, Yusriaina (JURISTA: Jurnal Hukum dan Keadilan, 2023)
This article aims to examine the application of Murabahah contract in Mitra Dhuafa Cooperative, in Kembang Tanjung District, Pidie Aceh, Indonesia. This study is written with a conceptual approach, namely with the type of research is doctrinal legal research. The results showed that the procedure for applying the murābaḥah contract for instalment services of Mitra Dhuafa Cooperative in Lancang Village, Kembang Tanjung District was carried out in two stages. Firstly, members apply for financing with the conditions that they must be women with low income, a group of at least 10 members, business financing, with the permission of their husbands or family members, complete photocopies of KTP, KK, details of the items to be purchased. Secondly, the implementation of the murābaḥah contract. At this stage two contracts are executed, first the wakalah contract, which is the cooperative representing the purchase of goods to members on behalf of the cooperative, followed by the murābaḥah sale and purchase contract. The implementation of the murābaḥah contract is in accordance with Sharia principles, without any elements of usury, gharar, maisir and zhulm. Nevertheless, Mitra Dhuafa Cooperative needs to pay attention to the members, must understand the process of the contract mechanism used, then members so that they carry out all their obligations in fulfilling the instalments.